Subcolectomy and symphyseal distraction-osteotomy using a spacer of spirally fashioned orthopedic wire: a treatment option for cats with pelvic canal stenosis, megacolon and obstipation - Fabiane Azeredo Atallah (Ciência Rural, 2016)
The use of two cerclages with wire spirals as distractor spacers was evaluated for the correction of pelvic stenosis in felines. A three-year-old, mixed-breed, male feline was taken to the Veterinary Hospital of the UFRJ. It presented symptoms of constipation, dyschezia, hyporexia and mild apathy. On radiographic examination, a deformation of the pelvic bones and a narrowing of the pelvic canal were detected. The patient underwent pelvic stenosis correction surgery. Two spirals were made with cerclage wire and 2.0-mm diameter Steinmann pins; coupled to the chuck of a drill, the pins were wrapped with cerclage wire, running laps around the pin. Then, the coils were positioned in the space formed by separating the hemipelves and stabilized by keeping them separated to the desired opening. Effectiveness of the technique was evidenced by measurements made using new radiographic images in comparison with the images obtained before the surgical procedure. There were evident decreases in the sacro-ischium line and pubic line of 3.98 and 3.18, demonstrating an increase of approximately 21% in the pelvic canal diameter. The animal showed no apparent macroscopic or radiographic reaction. The preliminary clinical application of the adapted pelvic distraction technique is relevant for allowing the appropriate correction of a stenosis of the pelvic girdle and its consequences, representing a major technical and scientific innovation in the correction.